(untitled) (Geologica Macedonica, 2015)
The phase transformations of the amorphous SiO2 have a very important role in the applicationof diatomite in the production of ceramic products. Therefore the phase transformations of diatomite are observedwith the use of DTA and TGA at temperatures up to 1100°C, and diatomite in powder state heated at temperature1000–1200°C for a period of 1 and 2 hours. DTA and TGA analyzis show that during thermal treatment up to 1100°Cthe diatomite remains in its amorphous phase. Roentgen-structural examinations of probes heated at 1000–1200°C fora period of 1–2 hours show no presence of crystalline phases at 1100°C. XRD examinations of probes heated at1200°C show presence of the crystalline phases cristobalite and quartz. The samples was heated at 1200°C for a periodof 2 hours, and was observed with an increase of the cristobalite content compared with quartz. SEM and TEMexaminations results of diatomite heated at 1200°C for a period of 2 hours show that the probes undergoes sinteringfollowed by reduced porosity.